Kualitas Produk Tradisional Sulam Tapis Mampu Memberikan Kesejahteraan Masyarakat di PKBM Permata Metro Lampung - Hendradewi, Savitri; Ningrum, Lestari; Suri, Muhammad Tri Rahardika; Festivalia, Filma (Jurnal Ilmiah Pariwisata, 2022)
This study aims to determine the effect of the quality of Lampung Tapis Embroidery products on the welfare of the community, especially the Lampung Tapis Embroidery artisans, which are one of the typical cultural heritages of Lampung Province that need to be preserved. This study uses a descriptive correlational method through a quantitative approach with simple regression analysis using the SPSS program. The sampling technique used is saturated sampling because the population is the same as a sample of 30 artisans at PKBM Permata Metro. The data collection technique was distributing questionnaires using a Likert scale of 1 to 5. The results showed that the quality of traditional Sulam Tapis products had no significant effect on Community Welfare at PKBM Permata Metro Lampung because the income that artisans got from PKBM Permata was less than Rp. 500,000, so the artisans felt income from Tapis Embroidery was insufficient for daily food and school children's needs. PKBM Permata Metro is advised to be able to increase learning hours in Lampung Tapis embroidery and provide visual and relevant learning so that artisans easily understand techniques and materials and improve discipline, as well as readjusting craftsman wages. Keywords: Carrying Capacity of Tourism, Sustainable Tourism